Pendampingan Bumdes Bima Sakti Welahan Jepara melalui Inovasi Produk Berbasis Limbah - Santi Andriani; Achmad Zainuddin; Amrina Rosyada; Ali Shofyan (IKIP PGRI Bojonegoro, 2019)
The partner of this program is the village’s business institution (Bumdes) in Karangayar Welahan Jepara named Bumdes Bima Sakti. The main issues are: 1) lack of awareness and knowledge of partners in waste management; and 2) lack of partner creativity in waste-based product innovation. The purpose of this community service program is to increase awareness, education, and also the creativity of partners in waste management and product innovation. The methods used are socialization, training, and evaluation. The results of this program are: 1) creation of waste-based products; 2) The results of the partner evaluation questionnaire regarding the program are very good with an average percentage of 90%.